Wattana-Atham (Cultural Injustice) Conceptual Art and Local Development: A Case Study of Phrae Hae Raberd - Suwannasa, Chestha; Pangkesorn, Anucha (DEC Journal : Art and Design, 2025)
This article examines the discourse of “Phrae Hae Raberd” as a discursive tool that suppresses and distorts local identity through the reproduction of negative cultural stereotypes within Thai society. The analysis is framed by the newly proposed concept of “Wattanatham” (Cultural Injustice), which serves to explain the mechanisms of cultural inequality embedded within centralized power structures and dominant discourses. This study explores the intersection between discourse and symbolic domination, and demonstrates how Conceptual Art can act as a critical mechanism for resisting oppression and revitalizing community identity. The case study of the “Hae Raberd Café” in Phrae province is analyzed as a community art space that employs creative cultural processes and artistic interventions to challenge negative stereotypes, foster public dialogue, and generate shared learning between locals and broader audiences. This process ultimately contributes to sustainable local development by restoring pride in collective identity. The findings suggest that both the concept of Cultural Injustice and Conceptual Art offer powerful theoretical and practical tools for analyzing, contesting, and transforming the cultural hegemony that shapes social perception in Thailand.